Subsidi di Indonesia - Anugrah Stephen Soen; Herry Sugianto; Ricky Theodorus; Supeni Anggraeni Mapusari (Universitas Warmadewa, 2022)
Subsidies are one of the tools for equitable distribution of welfare that the state can use to help low-income communities. The existence of subsidies allows the government to maintain economic stability and public welfare. One of the challenges in allocating subsidies in Indonesia, among others, is the vast territory of the country with a variety of diversity, so that the strategy adopted will also be unique. Therefore, the distribution mechanism also varies in terms of form, size, and procedure. This study discusses various kinds of subsidies that the government has provided. Various types and mechanisms of subsidies are discussed to facilitate subsidy mapping. In addition, this study also describes the subsidies carried out by the government during the pandemic. This detailed discussion of subsidies is expected to enrich the literature on subsidies based on practices that have been carried out in Indonesia. Many considerations need to be made by the government so that the budget provided for subsidies can meet the subsidy target by taking into account the financial capacity of the state. Subsidies in the APPBN Indonesia are also growing from year to year. The analysis in this article indicates that what the government has done from 2015 to 2019 has succeeded in building better human resources and providing good facilities to make Indonesia a decent place to live.